Research based learning conservation critical land in Meru Betiri National Park Indonesia - Ikhsan, Fahrudi Ahwan; Sumarmi, Sumarmi; Utaya, Sugeng (Intelektual Pustaka Media Utama, 2025)
Geography teacher candidates need to build a pro-environmental attitude to solve critical land issues through the construction of appropriate research-based solutions. This study aimed to determine the effect of research-based learning conservation on the pro-environmental attitudes of geography teacher candidates toward the preservation of Meru Betiri National Park. The study applied an experimental research design with one group pre-test and post-test. Students of the Department of Geography Education in the Faculty of Teacher Training and Education, at the University of Jember were selected as research subjects using purposive sampling. A total of 41 students currently enrolled in environmental geography courses took part in this study. The data on pro-environmental attitudes were collected using a 21-item Likert survey with scales: 1 (strongly disagree), 2 (disagree), 3 (agree), and 4 (strongly agree). The data were tested for normality and homogeneity using a t-test. The results implementation of conservation-based learning had a significant effect on the students’ pro-environmental attitudes on critical land in Meru Betiri National Park (p 0.000). Research-based learning has an impact on student’s scientific abilities and actions. Future research on conservation-based learning for sustainable conservation programs is recommended to involve forest farmers combine ecological and economic aspects of degraded lands.